An overview of binimetinib for the treatment of melanoma. (2nd May 2020) - Specenier, Pol
ABSTRACT: Introduction: Approximately 50% of patients with metastatic melanoma have mutations in BRAF. Based on the results of prior phase III trials, the combination of a BRAF inhibitor (BRAFi) and a MEK inhibitor (MEKi) is the standard of care in patients with BRAF-mutant metastatic melanoma. Areas covered: The author summarizes the available data on binimetinib, a reversible inhibitor of the kinase activity of MEK1 and MEK2, in BRAF- and NRAS-mutated melanoma. Expert opinion: With the advent of binimetinib and encorafenib, clinicians can choose between three BRAFi/MEKi combinations. Indirect comparison and a network meta-analysis suggest that binimetinib plus encorafenib is at least as active as the other two BRAFi/MEKi combinations and that safety is similar. The choice should be guided by the slightly different toxicity profile, local availability, and product experience. The optimal sequence of immunotherapy and BRAFi/MEKi in patients with BRAF-mutated tumors is unclear. As the response to BRAF/MEK inhibition is usually prompt and response to immunotherapy can be delayed, clinicians often choose a BRAFi/MEKi combination as first-line therapy in patients with rapidly evolving and threatening disease. Single-agent binimetinib almost doubled median progression-free survival when compared to dacarbazine in patients with NRAS-mutated melanoma.